Riflessioni sulle dimensioni della normatività: etica, deontologia e diritto. Il ruolo della deontologia in prospettiva comparata (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper aims to analyse form a comparative perspective the role of codes of medical ethics (CME) in the interplay of rules concerning medical assisted dying. In Europe CMEs are gaining growing attention, due to their ability to regulate important aspects of professional conduct, including end of life issues. Professional rules can complement the legal framework but can also turn out to be in contrast with legal provisions and in these conflicts medical ethics can act either as a source of law fostering the protection of patients’ rights or as a tool undermining it. After having analysed the legal value of CMEs from a comparative perspective, the essay sketches some of the most significant and multifaceted interactions between the law and the CMEs in the field of medical assisted dying in some European countries.
Keywords: code of medical ethics; medical assisted dying; legal pluralism; comparative public law; sources of biolaw